Stability analysis and enhancement for future power electronics-dominated power systems - Yu, Jiale (Nanyang Technological University, 2022)
Over the past few years, we have witnessed an increasing demand for renewable energy due to fossil energy scarcity and environmental concerns. As the trend continues, the power system will be fundamentally transformed to incorporate a high penetration level of renewable energy sources (RESs). Similar to other emerging technologies such as energy storage and electric vehicles, RESs are generally connected to the grid through power electronic converters. Therefore, future power systems will gradually shift to be power electronics-dominated from conventional synchronous generator-dominated form. Despite many advantages in control speed and flexibility, power electronic devices bring new challenges to the stability of power systems. On the system level, frequency instability is caused by the lack of inertia, tracing back to the increasing amount of power electronic converters in power systems; on the converter level, the stability issues are generated by both small-signal issues and large signal issues. In this thesis, the fundamentals of future power electronics-dominated power systems are first described, with two types of grid-connected converters - the grid-following (GFL) type and the grid-forming (GFM) type - introduced in detail. Then, the concept and modeling of virtual synchronous generators (VSGs) are presented. In addition, the above-mentioned stability issues are discussed. Both small-scale and large-scale electronics-dominated power systems with high renewable integration levels face the challenge of frequency instability, which is caused mainly by lack of inertia. The problem arises as RESs are connected to the grid through fast-response power electronics converters, which do not naturally provide any inertia, unlike conventional synchronous generators. To address this issue, several methods are compared. Firstly, independent energy storage systems (ESSs) can effectively carry out frequency regulation. Compared with other ESSs such as batteries and supercapacitors, flywheels’ advantages in providing inertia support are highlighted. Its performance in inertia emulation is presented in detail. Secondly, inertia emulation by one of the most widely used renewable energy, wind energy, is introduced. However, this method has its limitation: the rotor speed of the wind turbine needs to recover to its optimal value as soon as possible after the inertia emulation control period; during this recovery period, a secondary frequency drop would become obvious if too much energy is absorbed from the grid. To tackle this issue, a novel idea that uses DC-link capacitors to compensate for the power absorbed by wind turbines from the grid during the speed recovery period is proposed, in which the DC-link capacitor voltage changes accordingly. In general, for small-signal stability issues, small variations in the DC-link voltage is able to achieve the linear system model. However, for larger signals, the linear small-signal model will no longer be applicable, and an accurate large-signal modeling and stability analysis is required. Although small-signal modeling and stability analysis of grid-tied power converters have been well studied, three-phase power converters may exhibit strong nonlinearity and complex behaviors in the face of large DC-link reference voltage changing or large voltage deviation from the rated DC-side voltage at the start or re-start phase or the load transient process, where small-signal models are invalid. As such, a novel large-signal model—a modified state-space average model—of three-phase grid-tied power converters is proposed. Through the generalized phase portraits analysis, the proposed model accurately predicts stability problems and identifies stable regions as well as decisive design parameters. Also, the mechanism of instabilities is disclosed and elaborated. More importantly, a novel saturation controller based on space division is proposed, and the effect of stability improvement is further analyzed. Generally, grid-connected converters can be classified into GFL converters and GFM converters. It is unrealistic to control all the grid-connected converters as GFL-type converters in power systems. The GFM converters are indispensable for forming the voltage of the whole system. Compared with the GFL converter, a GFM converter behaves as a voltage source and can run autonomously even without the main grid. This attribute makes GFM converters a promising candidate to support the power grid frequency and voltage during islanding scenarios. Since the behaviors of GFM converters are closer to those of synchronous generators, it is envisioned that GFM converters will be widely used in future power electronics-dominated power systems. Grid synchronization stability is an important research topic for GFM converters. To prevent instability and undesired oscillations, the stability analysis must be performed, which requires the line impedance information. However, the line impedance may be unknown in most cases. Consequently, the designed control parameters may fail to satisfy the stability requirement. In this thesis, a geometrical approach to evaluate and improve the small-signal synchronization stability of GFM converters is introduced. The proposed analytical approach maps the line impedance variation on a two-dimension plane and identifies the stability boundary geometrically. As a benefit, the controller of GFM converters can be explicitly designed to achieve robust synchronization stability. As the renewable sources integration trend continues, new challenges and opportunities will emerge in power electronics-dominated power systems. For converter-level stability, large-signal stability analysis and enhancement of GFM-type converters require further research efforts; while for system-level stability issues, voltage instability remains a problem that needs further exploration.